ANTHOCYANINS: A HUE FOR HISTOLOGY - SYSTEMATIC REVIEW - Jasphin, Shiny; Parampalli Raghavendra, Archana; Charlotte Solomon , Monica; Amuthan , Arul; Mohan Kumar Singh , Brij; Valerina Kairanna , Nikitha (Malaysian Journal of Science, 2023)
Background: Many histological stains cause health hazards to technicians, pathologists, and researchers. The hazard-free and eco-friendly natural anthocyanins have the potential to be a new source for histological stains. This study aims to systematically review the use of plant products containing anthocyanin for histopathological diagnosis. Methods: A comprehensive literature search was done using suitable keywords on Wiley, PubMed, Scopus, Google Scholar, and Web of Science databases. A total of 30 articles were selected for systematic review, where data obtained from the studies were tabulated. Results: About 90% of the reviewed studies have proven that anthocyanin-containing plant products may be used as natural stains. Out of the 30 studies, 49% involved the use of Hibiscus extract, 11% utilised mulberry extract, 9% utilised pomegranate, another 9% involved rose, and the remaining ones utilised black plum, black rice, butterfly pea, the flame of woods, onion skin, and red poppy extracts. Almost 40% of the studies concluded that aqueous extracts are superior to alcohol ones, and 46% used either iron or alum as mordant. Conclusion: Natural stains containing anthocyanin could be a better alternative to synthetic histological stains. Further extensive studies should be conducted to observe the use of these stains in pathological diagnosis.